Strong, bold, and kind: Self-control and cooperation in social dilemmas - Martin G. Kocher; Peter Martinsson; Kristian Ove R. Myrseth; Conny Wollbrant (European School of Management and Technology (ESMT), 2013)
We develop a model that relates self-control and conflict identification to cooperation patterns in social dilemmas. As predicted, we find in a laboratory public goods experiment a robust association between stronger self-control and higher levels of cooperation. This means that there is evidence for an impulse to be selfish and that cooperative behavior requires self-control effort. Free-riders differ from other contributor types only in their tendency not to have identified a self-control conflict in the first place.
urn:nbn:de:101:1-2013071912532
Keywords: C91; D03; H40; 650; self-control; cooperation; public good; risk; experiment; Persönlichkeitspsychologie; Risikopräferenz; Öffentliche Güter; Spieltheorie; Test